Identifikasi Cemaran Bacillus Dan Khamir Pada Jamu Gendong Beras Kencur Dan Kunir Asam Di Pasar Gede Kota Solo - Mukhtar, Agung (2016)
Background: Liquid traditional herb is one of famous national unique characteristics of Indonesia. Its existence has been development of herbal plants in Indonesia. The use of herbs as medicine has been based on experiences of the nation's ancestors. Process of making liquid traditional herbs is very simple, namely parts of herb plant are taken and pulverizes them, then mixed it with water and squeezed to extract useful substances. On stage of herbal medicine procces was considered to still les hygienic. The herbal medicine beras kencur dan kunir asam were sold that not necessarily free from contamination of bacillus and yeast. Purpose: Purpose of the research is to know description if quality of beras kencur and kunir asam sold in Pasar Gede of Solo is meeting standard for consumption by people or not. Method: The research is a descriptive-qualitative one by observing level of bacillus and leaven contaminations and characteristics of contamination including colony morphology, cellular morphology and its properties. Bacterial contamination was observed by using serial method and leaven contamination was examined directly by using PDA method. Results: Results of the research indicated that the liquid traditional sold by person A were not meeting standards for consumption, those sold by person B and person D were considered to meet standards for consumption, and those sold by person C were meeting standards for consumption. Conclusion: Types of microbes found in the liquid traditional herbs sold in Pasar Gede of Solo were, among the others, Bacillus pumillus, Bacillus megaterium, Bacillus licheniformis, Bacillus subtillis and types of leaven were Aspergillus niger, penicillium sp, Monosporium sp